Diseminasi Pelayanan Penyaluran Transfer ke Daerah sebagai Upaya Peningkatan Pemahaman Stakeholder pada KPPN Mataram - Wijaya, Yoel Sthyeven (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Transfers to Regions (TKD) are an essential fiscal instrument for supporting regional governance and promoting equitable development. Effective TKD distribution requires stakeholders to have a comprehensive understanding of the applicable regulations and distribution mechanisms. This community service activity aimed to enhance stakeholders' understanding of the TKD distribution process through the Dissemination of Regional Transfer Distribution Services conducted within a Public Consultation Forum organized by KPPN Mataram. A descriptive qualitative approach was employed using observation, documentation, and Focus Group Discussions (FGDs) as data collection techniques. The findings indicate that the forum successfully improved participants' understanding of TKD distribution procedures, identified various administrative and technical challenges encountered by local governments, and generated recommendations to strengthen inter-institutional coordination, optimize information systems, reinforce KPPN's role as a Financial Advisor, and expand dissemination activities. Overall, the program contributed to improving public service quality, strengthening stakeholder collaboration, and supporting a more effective, transparent, and accountable regional transfer distribution system.